(3GUWdGMGJ GdUhajIs - (3YHO GdQRGb Hf CMeO Hf CHj GdZfGFe eMeO , LeGd GdOjf , GdcGTj,J (B730 (3g` s
(3ChdgG (B:s
(3hHYO aEfi deG aQZJ ef JShjO TQM cJGH efGRd GdSGFQjf gPg GdQSGdI Ydi bSejf bSe ai HjGf GdeUWdGMGJ eG YOG GdebGeGJ aEfgG s
(3BNQgG (B:s
(3GdafGA ai GdPGJ eY HbGA GdQSe GdNai GdefhQ HfhQ GdMb GdeTYQ HGdCKfjfjI GdeKHJI ddNdI JeJ hdjcf gPG BNQ eG CQOfG EjQGOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3HBNQg OYGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B350 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B215 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B567s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eMeO CMeO GdeMGei (B_ (3GdHUQI (B(219 (3N(B) s
Keywords: (3GdeLGejYs